Development of an intelligent system based on metaverse learning for students with disabilities - Sghaier, Souhir; Elfakki, Abir Osman; Alotaibi, Abdullah Alhumaidi (Frontiers in Robotics and AI, 2022)
According to what the world has undergone from the Corona pandemic, where people have resorted to work and study using the Internet, metaverse has been strengthened and become part of our life. The advent of the technology between the real and virtual worlds has facilitated the transmission of spatial audio and haptics, so metaverse can offer multisensory experiences in diverse fields, especially in teaching. The main idea of the proposed project is the development of a simple intelligent system for meta-learning. The suggested system should be self-configurable according to the different users of metaverse. Researchers have aimed to design and create a virtual learning environment using Open Simulator based on a 3D virtual environment and simulation of the real word environment. Then we connect it to the learning management system (Moodle) through the technology of 3D virtual environments (Sloodle), i.e., managing students, especially the disabled ones, and following up on their activities, tests and exams. Besides, it has the advantage of storing educational content. We evaluate the performance of the Open Simulator in both the grid and standalone modes. The evaluation is done according to the login time measures. The result shows that the time in each standalone mode is 12 seconds and grid Mode 16 seconds, which proves that the proposed platform is very robust. The system is also tested on 50 disabled learners, according to the t-test of independent samples. A test is conducted in the mathematics course, where the students are divided into two equal groups, 25 students traditionally take the test, and 25 students take the test using the chair test tool. It is one of the most important tools of the Sloodle technology. According to the results, the null hypothesis is rejected, and we accept the alternative hypothesis that presents a difference between the achievement of the two groups.